1β, 25-Dihydroxyvitamin D3: A new vitamin D metabolite in human serum. Issue 173 (October 2017) - Pauwels, Steven; Jans, Ivo; Billen, Jaak; Heijboer, Annemieke; Verstuyf, Annemieke; Carmeliet, Geert; Mathieu, Chantal; Maestro, Miguel; Waelkens, Etienne; Evenepoel, Pieter; Bouillon, Roger; Vanderschueren, Dirk; et al.
Abstract: Background: The measurement of 1α, 25(OH)2 D3 in human serum poses a true challenge as concentrations are very low and structurally similar metabolites can interfere. Materials and methods: During optimization of our in-house LC–MSMS method for serum 1α, 25(OH)2 D3 a previously co-eluting isobaric interference was separated. The isobar was identified as 1β, 25(OH)2 D3 by comparing retention time and fragmentation spectra to standards (other isobaric dihydroxylated vitamin D3 analogs). 1β, 25(OH)2 D3 showed specific cluster formation (water), not present in 1α, 25(OH)2 D3 . 1β, 25(OH)2 D3 was measured in serum of apparently healthy human volunteers (n = 20), patients with high serum 25-hydroxyvitamin D [25(OH)D] concentrations (>50 ng/mL) (n = 33 among which 4 with very high levels (>150 ng/mL)) and patients with kidney failure (n = 68; 39 stage 1–3, 29 stage 4–5). Pearson's r was calculated for correlations and Mann-Whitney statistic to compare group medians. Results: Median serum 1β, 25(OH)2 D3 was 11 pg/mL in apparently healthy volunteers and increased to 20 pg/mL for serum 25(OH)D concentrations above 80 ng/mL (n = 22) (p < 0.0001). 1β, 25(OH)2 D3 concentrations were significantly correlated to serum 25(OH)D concentrations (r = 0.85) for the combined results from healthy volunteers and patient sera (n = 53) (p < 0.0001). For patients with kidney failure, median serum 1β, 25(OH)2 D3 was 7 pg/mL and not different from the median level in healthy volunteers (p = 0.06). The median concentration did not vary with different stages. Conclusions: We present evidence for the widespread presence of 1β, 25(OH)2 D3, a new vitamin D metabolite, in human serum. The level increases with rising serum 25(OH)D concentrations and is particularly high in patients with very high 25(OH)D levels. We previously demonstrated that 1β, 25(OH)2 D3 is a poor genomic agonist but a potent non-genomic antagonist of 1α, 25(OH)2 D3. The clinical implications of the presence of this analog therefore require further exploration.